The Effect of Sea State on the Polarization of Reflected Beidou B1 Signals - Lyu, Tingting; Sha, Shuang; Zhang, Min; Zhang, Hao; Gulliver, Thomas A. (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: Oceanographic buoys generally employ satellites for positioning and data transmission. However, sea surface conditions can affect these signals. The Signal to Noise Ratio (SNR) of small observation buoys can be improved by exploiting polarization diversity. Methods: This paper discusses the effect of sea surface conditions on the polarization and reflection loss of Beidou B1 reflected signals for the purposes of exploiting polarization diversity. The Rayleigh roughness criterion is used to assess the roughness of the sea surface. The Fresnel reflection coefficients are derived to analyze the polarization and reflection loss of the Beidou B1 reflected signals with different sea surface states. Results: The results obtained show that for the Beidou B1 signals, the sea surface is considered rough for most sea surface states and incident angles. For smooth sea surfaces, the Beidou B1 reflected signals are mainly Left Hand Circularly Polarized (LHCP) waves, but Right Hand Circularly Polarized (RHCP) waves dominate when the incident angles are larger than the Brewster angle. The reflected loss is between -2 dB to -3.4 dB. In rough sea surfaces and the signals propagation is dominated by diffuse reflection. The reflection loss decreases with the incident angle and there is a fluctuation when the incident angle is around 49 degrees. The specular reflection signal has a significant amplitude when the angle of incidence is large. RHCP waves are the main component of the reflected signals, and the reflection loss is relatively small which can be employed for polarization diversity or marine remote sensing. Conclusion: polarization diversity is only useful with good sea conditions, and the corresponding gain decreases with the deterioration of the sea surface conditions.
Keywords: polarization diversity